A New Attestation of the Cult of Zeus Trossou in a Public Inscription from the Upper Maeander River Valley (Çal Ovası) - Esengül Akıncı Öztürk; Hasan Baysal; Marijana Ricl (Gephyra, 2015)
This article contains the publication of a new public inscription from the village of Akkent north of Çal (ancient Atyochorion). The inscription dates from the Roman Imperial period and its upper half is heavily damaged. The remaining part of the inscription contains information about a local benefactor Pl. Eukopos, son of Philodoxos (?), who donated 150 denarii for the sacrifices of oxen to Zeus Trossou and for the payment of the priests' poll tax, under the condition that the expenses are perpetually defrayed from the interest, while the principal remains intact to the people. The lost part of the inscription contained a list of similar dedications/donations, erected under the supervision of the members of local gerousia.